It’s textbook: controlling the narrative about residential schools in Ontario classrooms - White, Connor (Information Research an international electronic journal, 2025)
Introduction. Between 1831 and 1996, 149 residential schools were established in Canada with the purpose of assimilating young Indigenous children by stripping them of their language, culture and history. However, residential schools have been historically absent as a topic of study in Ontario primary and secondary school classrooms. Method. This study examines the way curricula and textbooks approved for use in Ontario classrooms by the Ministry of Education between 1998 and 2024 help control information taught to students about residential schools. Analysis. These materials are analysed to examine the evolution in the number of times residential schools are mentioned as well as the quality of these descriptions to better understand the culture of information control which surrounds the topic of residential schools. Results. These educational materials contain a lack in both quantity and quality in the description of residential schools despite a slight increase in the number of times residential schools are mentioned in these materials after 2013. Conclusions. These results reflect the effects of political information control on educational materials and its impact on the way residential schools have been relegated to the margins of Canadian history in favour of a nationalistic White settler colonial narrative.